HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEPATUHAN MENGKONSUMSI TABLET Fe PADA REMAJA PUTRI DI WILAYAH KERJA PUSKESMAS MINASA UPA MAKASSAR - Ramlah Ramlah; Andi Syintha Ida; Djuhadiah Saadong; Fitriati Sabur (Jurnal Inovasi Penelitian, 2022)
Anemia is a condition when the number of red blood cells or the concentration of oxygen carriers in the blood hemoglobin (Hb) is insufficient for the physiological needs of the body. Anemia often affects women of childbearing age. This is because there is a menstrual cycle in women every month. Lack of iron can reduce endurance so that it can cause decreased productivity. The purpose of this study was to determine the relationship between knowledge and attitudes with adherence to consuming Fe tablets in young women. The research method was analytical survey with a cross sectional approach and the sample was taken using a total sampling technique of 41 people. The study was conducted in April-May 2021 using a questionnaire instrument. Analyzed by bivariate using chi square test.The results of the univariate analysis showed that respondents with a fairly good knowledge were 26 respondents (63.4%), the attitudes of young women in the positive category were 33 respondents (80.5%), and 25 respondents were obedient to consuming Fe tablets (61, 0%). The results of the bivariate analysis showed that the knowledge (Pvalue = 0.036) and the attitude of young women in consuming Fe tablets (Pvalue = 0.020). The conclusion is that there is a relationship between knowledge and attitude with compliance with consuming Fe tablets